Systematic Review: Enhancing Photovoltaic Performance through Hydrophobic Surface Coatings and Heat Mitigation - Pawawoi, Andi Pawawoi; Refdinal, Refdinal Nazir; Hamid, Muhammad Imran Hamid (Jurnal Teknik Elektro, 2024)
Surface coatings are essential for improving the performance of photovoltaic (PV) modules, particularly in challenging environments such as hot and dusty tropical regions or low-radiation subtropical areas. This study reviews recent developments in hydrophobic and heat-mitigating coatings that address two main problems: soiling and overheating. Both issues significantly reduce the efficiency and lifetime of PV systems. By systematically reviewing 32 selected studies, this paper identifies coating materials that combine self-cleaning, thermal regulation, and optical benefits. Among them, three-layer superhydrophobic coatings, silica–silane nanocomposites (e.g., SiO₂–PDMS, HDTMS–SiO₂), and Al₂O₃–H₂O nanofluids showed remarkable improvements in power output, optical transmission, and heat dissipation. For example, a three-layer superhydrophobic coating increased output power by 195.2% under simulated drizzle with heavy soiling, while SiO₂–PDMS nanocomposite films reduced surface temperature by 3.5 °C without reducing efficiency. These findings confirm that coating selection must balance hydrophobicity, heat management, durability, and cost. This review also highlights research gaps, particularly in long-term durability testing and large-scale application. The results provide practical guidelines for selecting appropriate coatings in different climates and suggest directions for developing multifunctional and scalable PV surface technologies.